INTEGRATION OF PERFORMANCE MANAGEMENT WITH RISK MANAGEMENT USING THE RISK-BASED PERFORMANCE MANAGEMENT MODEL TO IMPROVE COMPANY PERFORMANCE - Andri Sahputra; Meilita Tryana Sembiring; Nazaruddin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to formulate an integrated model for performance and risk management through a Risk-Based Performance Management (RBPM) approach to improve company performance at PT XYZ, an airport operator. The research is motivated by the continued failure to meet several performance indicators, suboptimal operational cost efficiency, and the lack of integration between risk management and performance management, which prevents risk information from fully supporting strategic decision-making. In addition, the results of the risk maturity assessment indicate that there are still gaps in governance, process integration, and the use of risk data and technology. The study uses a qualitative descriptive approach with a case study at PT XYZ. Data were obtained through analysis of company documents, performance reports, risk profile reports, Risk Maturity Index (RMI) assessment results, observations, and interviews with related work units. The analysis compared the existing conditions of performance management and risk management implementation with the Risk-Based Performance Management framework to identify gaps and formulate improvement plans. The results show that performance management and risk management are still running partially, risk appetite has not been consistently internalized in target setting, and performance indicators, risk indicators, and control indicators are not yet connected in an integrated system. The RBPM model is designed to integrate Key Performance Indicators (KPIs), Key Risk Indicators (KRIs), and Key Control Indicators (KCIs) through strategic alignment, risk appetite, dashboard-based monitoring, and an early-warning system. Implementing this model can improve decision-making quality, strengthen governance, enhance organizational resilience to uncertainty, and encourage more stable, measurable, and sustainable performance.